The influence of post-diuretic late phase imaging in visual and quantitative evaluation of urothelial tumors by F-18 fluorodeoxyglucose positron emission tomography/computed tomography - Koç, Zehra Pınar (Turk J Urol, 2019)
OBJECTIVE: Although F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) is a valuable imaging method in most of the malignant tumors, it is considered to have limited diagnostic ability in urothelial tumors due to high physiologic urine activity. The aim of the present study was to evaluate the effect of post-diuretic late phase imaging to the visual and quantitative evaluation of urothelial tumors in the staging and restaging of the patients. MATERIAL AND METHODS: Two patients with ureter and 40 patients with bladder tumors (6 females and 36 males, mean age: 67.12±8.79 years) who were referred for staging or restaging or treatment response evaluation to the F-18 FDG PET/CT were included in the study. Late phase (at the second hour after FDG injection) images including the renal pelvis and bladder region after the administration of approximately 40 mg furosemide were obtained after standard oncologic F-18 FDG PET/CT imaging. The images were evaluated by visual and quantitative interpretation, and index values were calculated. Paired samples T test was used to decide the significance of the difference between the early and late phase images. A p value <0.05 was considered significant. RESULTS: The activity accumulation in the primary or recurrent lesions in the bladder or ureter in the early and late phase images was statistically significantly different. Additionally, in 15/41 (37%) patients, the primary tumor in the bladder was only determined in late phase images, and additional lymph node metastases adjacent to the bladder or ureter were only observed in diuretic late phase images in some of the patients. The sensitivity, specificity, and diagnostic accuracy of the PET/CT with this methodology for N staging and M staging were 67%, 78%, and 82% versus 80%, 91%, and 82%, respectively. CONCLUSION: Late phase imaging after diuretic administration should be performed in case of non-visualization of primary tumor in the bladder region. The late phase post-diuretic imaging revealed significant improvement in the visual and quantitative diagnostic performance of the FDG PET/CT and has high diagnostic accuracy for the staging of urothelial tumors.